Meningkatkan Kompetensi dan Peluang Siap Kerja melalui Program Beasiswa di Bidang Teknologi Informasi - Wiyanti, Fiana Dwi; Irbayuni, Sulastri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The increasing need for workers in the information technology industry isn't in line with the education gap in Indonesia. One thing that can be solved to overcome this is providing scholarships in the information technology industry to provide financial assistance to support the education being pursued. PT Hacktivate Teknologi Indonesia (Hacktiv8) as a training institution of information technology that transforms beginners into digital talents also plays a role in combating this educational gap by providing Fullstack Javascript and Fulltime Data Science scholarship programs at the Hacktiv8 Surabaya Campus. This research uses qualitative research methods and uses primary and secondary data. The scholarship program was awarded to 6 selected participants who passed the acceptance test selection from 215 applicants. Scholarships are awarded with a full or partial scholarship scheme. Bootcamp education will be run according to the chosen program to improve competencies and skills that support work readiness and global competence.